2021
DOI: 10.1007/s12144-020-01341-8
|View full text |Cite
|
Sign up to set email alerts
|

Fear of missing out and self-esteem as mediators of the relationship between maximization and problematic smartphone use

Abstract: Problematic smartphone use (PSU), which involves an excessive and uncontrolled use of smartphones, thereby causing daily-life disturbance, has been associated with a range of negative outcomes including anxiety, depression, and deficits in social relationships. However, the relationship between PSU and maximization, which could be an explanatory factor, has not yet been thoroughly studied. Drawing on the Interaction-Person-Affect-Cognition-Execution (I-PACE) model, the current study aimed to investigate the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 59 publications
3
27
0
5
Order By: Relevance
“…For example, many studies have found that FOMO mediates relations between negative emotions (such as anxiety and depression) and PSU severity (35,37). It has also been found that FOMO plays a mediating role in maximization and PSU (33). Therefore, we can assume that FOMO plays a mediating role between stress and PSU severity.…”
Section: Background On Problematic Smartphone Use and Stress Fear Of Missing Outmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, many studies have found that FOMO mediates relations between negative emotions (such as anxiety and depression) and PSU severity (35,37). It has also been found that FOMO plays a mediating role in maximization and PSU (33). Therefore, we can assume that FOMO plays a mediating role between stress and PSU severity.…”
Section: Background On Problematic Smartphone Use and Stress Fear Of Missing Outmentioning
confidence: 89%
“…People who score higher in FOMO are more likely to overuse their smartphones to satisfy the desire to stay connected (32). FOMO and PSU are positively correlated, and higher FOMO can be a driver of PSU (33). A study by Elhai et al (34) found that FOMO is closely related to negative emotions, social use of smartphones, and PSU severity.…”
Section: Background On Problematic Smartphone Use and Stress Fear Of Missing Outmentioning
confidence: 99%
“…Previous studies have empirically investigated the reliability of FoMO as well as its relationship with social media addiction and PSU, among others (see [15], for a review). Additionally, other studies have reported direct and indirect associations of FoMO with PSU as well as its mediating role [5,[24][25][26][27].…”
Section: The Mediating Role Of Fear Of Missing Outmentioning
confidence: 92%
“…Recently, it has been suggested that PSU shares some commonalities with the construct of internet-use disorder, since smartphones are the most common way for individuals to access online social media applications [3]. Empirical studies have indicated that PSU can lead to severe psychological impairments for a minority of individuals, including anxiety (see [4], for a review, low self-esteem [5], and low self-control [6,7]. Additionally, PSU has been associated with poor sleep quality [8] and poor academic outcomes [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the (small-to-moderate) correlations between excessive digital technology use and depression and anxiety symptom severity are well-documented (Elhai et al, 2017 , 2020a ; Rozgonjuk et al, 2018 ). In addition, correlations have been found with variables that are closely associated with depression and anxiety, such as emotion dysregulation (Hoffner and Lee, 2015 ; Spada and Marino, 2017 ; Rozgonjuk and Elhai, 2020 ), fear of missing out (Hamutoglu et al, 2020 ; Rozgonjuk et al, 2020c ; Servidio, 2021 ), and negative affectivity (Elhai et al, 2018 ; Li et al, 2020 ; Zeng et al, 2021 ). These findings may hint that individual differences in personality traits—relatively stable characteristics over time—could drive these relationships (Marengo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%